2018
DOI: 10.21315/aamj2018.23.2.4
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents of Consumer-Based Electronic Retail Brand Equity: An Integrated Model

Abstract: The purpose of this study is to test and compare multiple conceptual models that examine the relationships among electronic retail (e-retail) service quality, trust, satisfaction, and consumer-based e-retail brand equity. A quantitative survey was conducted among Chinese online shoppers. The survey used established scales to measure constructs in the proposed models. Structural equation modelling (SEM) procedure was applied to test alternate models. The results confirmed that web design and customer service po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 94 publications
(163 reference statements)
0
4
0
3
Order By: Relevance
“…Konsumen yang merasa produk tersebut bermanfaat secara ekologis lebih cenderung membelinya. Butt et al (2018)menemukan bahwa green brand image suatu produk dapat memengaruhi minat beli konsumen melalui proses citra diri. Konsumen yang peduli dengan lingkungan lebih suka membeli barang-barang yang akan membantu mereka merasa bahwa mereka adalah konsumen yang telah berkontribusi terhadap pelestarian lingkungan.…”
Section: Pendahuluanunclassified
“…Konsumen yang merasa produk tersebut bermanfaat secara ekologis lebih cenderung membelinya. Butt et al (2018)menemukan bahwa green brand image suatu produk dapat memengaruhi minat beli konsumen melalui proses citra diri. Konsumen yang peduli dengan lingkungan lebih suka membeli barang-barang yang akan membantu mereka merasa bahwa mereka adalah konsumen yang telah berkontribusi terhadap pelestarian lingkungan.…”
Section: Pendahuluanunclassified
“…Marín-García et al (2021) highlighted a significant favorable influence of congruence between brand equity dimensions and (real) human personality on the level of consumer satisfaction. Butt et al (2018) suggested that brand equity would significantly impact consumer loyalty via their level of satisfaction with the brand. A brand is an exciting, pleasing, and satisfying feeling consumers experience when using a specific product (Kurniawati, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…En el clúster 2 (verde) se agrupan los estudios que investigan sobre los antecedentes, el rol mediador y los modelos de la lealtad en el comercio electrónico (e-commerce), y donde la satisfacción se estudia como resultado o antecedentes mas no como objetivo propio del estudio, por ejemplo, Butt et al (2018) quienes compararon múltiples modelos conceptuales que examinan las relaciones entre la calidad del servicio del comercio electrónico (e-retail), la confianza, la satisfacción y el valor de la marca del comercio electrónico basado en el consumidor. Ghazali et al (2016) quienes examinan la influencia de las barreras al cambio en la retención de clientes (es decir, e-loyalty) y los efectos moderadores de los costos de cambio y el atractivo de las alternativas.…”
Section: Identificación De Relacionesunclassified
“…1. insatisfecho vs satisfecho 2. infeliz vs feliz 3. desagradable vs agradable Butt et al (2018) La confianza y la satisfacción en línea se midieron utilizando las escalas del estudio de Ribbink et al (2004) sobre el comportamiento de los consumidores en línea.…”
Section: Ramezani Y Shokouhyar (2020)unclassified